Vitamin D in male sexual functions: unwrapping the sunshine hormone activities in erectile function and beyond - Odetayo, Adeyemi Fatai; Bassey, Grace Edet; Fajemidagba, Grace Ayobami; Okesina, Kazeem Bidemi; Hamed, Moses Agbomhere (Frontiers in Reproductive Health, 2025)
BackgroundVitamin D, sometimes referred to as the “sunshine vitamin”, is well-known for its role in maintaining bone health processes that are highly dependent on calcium regulation. However, there is an emerging wealth of evidence that this fat-soluble vitamin has an important role in male sexual health regarding erectile function, production of testosterone, and overall fertility. Due to the increased vitamin D deficiency rates in most populations, the implications of its deficiency on male sexual functions have gained great interest.Materials and methodsThis review, therefore, sums up recent publications that detail the association of vitamin D with male sexual functions regarding its potential roles in erectile function regulation, testosterone levels, and semen characteristics.ResultsVitamin D contributed positively to sexual and erectile functions. These were mediated via hormone-dependent mechanisms through its inhibitory role on prolactin and steroidogenic activities. It also improves endothelial functions by stimulating the secretion and release of nitric oxide, which is important for erection. Furthermore, it acts by mediating the activities of monoamine neurotransmitters, which are responsible for the motor activities involved in sexual function.ConclusionVitamin D acts via multiple mechanisms to enhance sexual and erectile functions.